Kompetensi kaunseling pelbagai budaya dan kompetensi spiritual dalam kalangan kaunselor berdaftar di Malaysia - Mohd Dagang, Mazidah; Abdul Kadir, Rusnani; Mohd Noah, Sidek; Baba, Maznah (Penerbit Universiti Malaysia Terengganu, 2013)
This study aimed to examine the level of spiritual competence and multicultural counselling competence among registered counselors in Malaysia. This study also would like to identify the different levels of spiritual competence and multicultural counseling competence based on demoghraphic factors such as gender, age, religion, ethnicity, educational level and tenure approval. A survey was conducted by administering a set of questionnaire consisting "the spiritual competency scale" by Young, Cashwell, Wiggins-Frame and Belaire (2002) and "Multicultural Competency Inventory" by Sodowsky, (1993). Both scales have been translated to Malay language. A total of 240 registered counselors participated in this study. The results showed that most counselors have a moderate level of spiritual competence with a mean of 3.64 as well as moderate level of multicultural competence with a mean of 2.78. In terms of differences in the level of spiritual competence, there is no significant differences based on gender, age, education level and years of service. Only the religious and ethnicity factor has a significant difference in the levels of counselors' spiritual competence. As for multicultural competence, there is a significant difference in age factor. Therefore, some suggestions have been made based on the findings of this study.